2017
DOI: 10.1007/s00540-017-2316-4
|View full text |Cite
|
Sign up to set email alerts
|

Continuous intraoperative epidural infusions affect recovery room length of stay and analgesic requirements: a single-center observational study

Abstract: PURPOSE Continuous intraoperative epidural analgesia may improve post-operative pain control and decrease opioid requirements. We investigate the effect of epidural infusion initiation before or after arrival in the post-anesthesia care unit on recovery room duration and post-operative opioid use. METHODS We performed a retrospective chart review of abdominal, thoracic and orthopedic surgeries where an epidural catheter was placed prior to surgery at the University of Washington Medical Center during a 24 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…The multivariate analysis found that iTEA at PACU arrival was a significantly associated factor of severe pain at discharge from PACU and admission to the ward (adjusted OR of 4.77) compared to patients with effective TEA at PACU arrival. This result is similar to that a study by Shah et al 6 ., which demonstrated that intra-operative epidural management predicted pain level, PACU length of stay, and PACU opioid use.…”
Section: Ineffective Thoracic Epidural Analgesiasupporting
confidence: 93%
See 1 more Smart Citation
“…The multivariate analysis found that iTEA at PACU arrival was a significantly associated factor of severe pain at discharge from PACU and admission to the ward (adjusted OR of 4.77) compared to patients with effective TEA at PACU arrival. This result is similar to that a study by Shah et al 6 ., which demonstrated that intra-operative epidural management predicted pain level, PACU length of stay, and PACU opioid use.…”
Section: Ineffective Thoracic Epidural Analgesiasupporting
confidence: 93%
“…Thoracic epidural analgesia (TEA) is widely used to manage post-operative pain after major abdominal and thoracic surgery [1][2][3][4] and is considered superior to other methods in managing and reducing post-surgical pain [1][2][3][4][5] . In addition, it facilitates the recovery of bowel function [3][4][5] and reduces the length of hospital stay in open abdominal surgery 3,6 . It has been well-documented to improve the patient's quality of life after surgery 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Majority of studies, some of them with large sample sizes, have demonstrated significant benefits of EDA for patients' comfort and outcomes (17,44,49,50), with the study of Monaco and co-workers (48) being an example. They investigated 459 consecutive patients with open thoraco-abdominal aortic aneurysm repair, with 409 (89%) patients receiving thoracic EDA (TEA).…”
Section: Efficacymentioning
confidence: 99%
“…Complications after epidural puncture are rare but may have dramatic effects including paraplegia (68). However, the currently available literature suggests that the benefits of EDA outweigh its risks and side effects (44,46,49,50,69,70). Thoracic epidurals are inserted in close vicinity to the spinal cord; the procedure has to be performed by experienced professionals (71).…”
Section: Complicationsmentioning
confidence: 99%
“…Traditionally, quality improvement efforts have focused on methods to streamline the TEA placement process, limit delays related to TEA placement on the overall operating room work ow and improve compliance with intraoperative epidural infusion. (10)(11)(12)(13)(14) While most of these improvement measures address local departmental issues, there are limited data on TEA surveillance at a system-level. We therefore conducted a retrospective observational study to explore the prevalence of intravenous opioid rescue analgesia in the post-anesthesia care unit (PACU-OpResc) in patients with TEA and evaluated the feasibility of this measure as a marker of TEA failure.…”
Section: Introductionmentioning
confidence: 99%